Comparative analysis of the Spanish autonomous communities’ policies on emigration and citizenship abroad, 1983-2012 - Oiarzabal, Pedro; Uzcanga, Catalina; Bartolomé, Edurne (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Currently, more than two million Spanish people live officially abroad. Since the 1980s, both the Spanish and some of the autonomous community governments have begun to recognise and support their respective emigrant populations. The paper analyses comparatively the evolution of the legislation that has made possible the establishment of civil servant structures and the development of services and programmes that specifically focus on the emigrant population by the central government as well as by ten of the autonomous communities with the greatest number of people abroad. From a methodological point of view, the research is based on the analysis of the complex legislative frame and services and programmes developed and on qualitative interviews with politicians and high ranking public servants in charge of emigration matters. The paper points out the urgent need for collaboration among the different public administrations and the update of emigration policies in the context of economic crisis, the loss of population and the increase of emigration flows.